Nuclear Power and Japan's Collective Future: Understanding Beliefs About How Nuclear Policies Will Affect Society. (30th October 2015) - Park, Joonha; Bain, Paul; Kusumi, Takashi
Abstract : Despite ongoing controversies regarding possible directions for the nuclear plants program throughout Japan since the Fukushima disaster, little has been researched about people's belief structure about future society and what may affect their attitudes toward different policy options. Beyond policy debates, the present study focused on how people see a future society according to the assumptions of different policy options. A total of 125 students at Japanese universities were asked to compare a future society with society today in which one of alternative policies was adopted (i.e., shutdown or expansion of nuclear reactors) in terms of characteristics of individuals and society in general. While perceived dangerousness of nuclear power predicted attitudes and behavioural intentions to make personal sacrifices for nuclear power policies, beliefs about the social consequences of the policies, especially on economic development and dysfunction, appeared to play stronger roles in predicting those measures. The importance of sociological dimensions in understanding how people perceive the future of society regarding alternative nuclear power policies, and the subtle discrepancies between attitudes and behavioural intentions, are discussed.